2017
DOI: 10.1002/cbic.201700251
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Structural Space of the Galectin‐1–Ligand Interaction

Abstract: Galectin-1 is a tumor-associated protein recognizing the Galβ1-4GlcNAc motif of cell-surface glycoconjugates. Herein, we report the stepwise expansion of a multifunctional natural scaffold based on N-acetyllactosamine (LacNAc). We obtained a LacNAc mimetic equipped with an alkynyl function on the 3'-hydroxy group of the disaccharide facing towards a binding pocket adjacent to the carbohydrate-recognition domain. It served as an anchor motif for further expansion by the Sharpless-Huisgen-Meldal reaction, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The present study also suggested that the number of H-bond interactions was significantly increased for all the dietary polyphenols found in the water environment, as discussed in the subsequent section on the MD simulation analyses. Another research on the crystallographic complex of human galectin-1 bound to LacNAc revealed some unexplored cleft on the galectin-1 protein surface constituting the amino acid Asp25 and Asp126 mediating the tailor-made ligand binding interactions [ 95 ]. In addition, the present study demonstrated the binding interactions of a few close proximity residues (Ser29 and Asp123) adjacent to the CRD region with the identified polyphenols, mimicking the binding interaction of LacNAc with galectin-1.…”
Section: Resultsmentioning
confidence: 99%
“…The present study also suggested that the number of H-bond interactions was significantly increased for all the dietary polyphenols found in the water environment, as discussed in the subsequent section on the MD simulation analyses. Another research on the crystallographic complex of human galectin-1 bound to LacNAc revealed some unexplored cleft on the galectin-1 protein surface constituting the amino acid Asp25 and Asp126 mediating the tailor-made ligand binding interactions [ 95 ]. In addition, the present study demonstrated the binding interactions of a few close proximity residues (Ser29 and Asp123) adjacent to the CRD region with the identified polyphenols, mimicking the binding interaction of LacNAc with galectin-1.…”
Section: Resultsmentioning
confidence: 99%
“…119 Indeed, further NMR investigations combining glycan array screening with NMR spectroscopy allowed deducing that the interaction of heparin hexasaccharides to the elusive secondary site did not require the presence of Ca 2+ ions, while activated an intradomain allosteric network of langerin that had previously been identified, although it was just linked to the affinity and release of Ca 2+ ions. 120 As a landmark in the field, combining multivalent presentation with NMR, an elegant series of asymmetrically branched precision glycooligomers have been built using chemical synthesis to study multivalent lectin-sugar interactions, such as in the Fig. 20.…”
Section: C-type Lectins: Dc-sign and Langerinmentioning
confidence: 99%
“…Indeed, further NMR investigations combining glycan array screening with NMR spectroscopy allowed deducing that the interaction of heparin hexasaccharides to the elusive secondary site did not require the presence of Ca 2+ ions, while activated an intradomain allosteric network of langerin that had previously been identified, although it was just linked to the affinity and release of Ca 2+ ions. 120 …”
Section: Introductionmentioning
confidence: 99%
“…[23,24] The more stable mutant CSGal-1, in which all six cysteines are replaced by serines, is often used for analytical studies. [25] Several X-ray and NMR structures are available of Gal-1 and CSGal-1, [25][26][27][28][29][30] demonstrating that lactose/LacNAc binding occurs via several direct hydrogen bonds established to amino acid residues in the carbohydrate binding site (H44, R48, H52, N61, E71) (Figure 1). Water networks are also important players in the carbohydrate recognition by Gal-1.…”
Section: Introductionmentioning
confidence: 99%
“…Several X‐ray and NMR structures are available of Gal‐1 and CSGal‐1, [25–30] demonstrating that lactose/LacNAc binding occurs via several direct hydrogen bonds established to amino acid residues in the carbohydrate binding site (H44, R48, H52, N61, E71) (Figure 1). Water networks are also important players in the carbohydrate recognition by Gal‐1 [31] .…”
Section: Introductionmentioning
confidence: 99%